Counting Advanced Precancerous Lesions as True Positives When Determining Colorectal Cancer Screening Test Specificity. (4th February 2022) - Ladabaum, Uri; Church, Timothy R; Feng, Ziding; Ransohoff, David F; Schoen, Robert E
Abstract: The landmark Centers for Medicare & Medicaid Services (CMS) decision memo on blood-based biomarkers to screen for colorectal cancer (CRC) sets thresholds of 74% or higher for sensitivity and 90% or higher for specificity for CRC. This approach does not consider detection of advanced precancerous lesions as true positives. We contrasted the impact of counting advanced precancerous lesions as true vs false positives and projected CRC outcomes under contrasting tests in a validated model. A test with the threshold performance set by CMS decreased CRC incidence by 30% and CRC mortality by 48% in individuals aged 45 years. If this test also detected advanced precancerous lesions with 30% sensitivity, CRC incidence decreased by 45% and mortality by 58%, but the CRC specificity of the test of only 88% would not satisfy the CMS threshold. CMS should reconsider its definition of threshold specificity for CRC screening biomarkers. Future coverage determinations on biomarkers to screen for cancer should consider detection of relevant precursor lesions and projected outcomes.